Cooperative Scheduling Strategy of Energy Storage Systems for Regional Grid Supplied by Renewable Energy - Rui MA; Xiangjun LI; Wenqi LI; Dongxue GAO; Jingchao ZHANG; Ningxi SONG (发电技术)
With the decrease of fossil energy reserves and the deterioration of natural environment, increasing the proportion of renewable energy in power grid becomes the main goal of power grid development in the future. Considering the constraints of energy storage systems, hydropower station, photovoltaic power station, wind farm and power grid operation, a cooperative scheduling strategy of energy storage systems in the regional power grid with renewable energy was proposed, and an optimal scheduling model was established. The optimization objective function was the maximum consumption rate of new energy and the output in the regional power grid. In order to improve the accuracy, the model was transformed into a mixed integer linear programming problem to solve. Finally, a modified IEEE 9-node system was used for simulation verification.